2020
DOI: 10.3390/jmse8120977
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of an Empirical Dune Growth Model for Evaluating Barrier Island Recovery from Storms

Abstract: Coastal zone managers require models that predict barrier island change on decadal time scales to estimate coastal vulnerability, and plan habitat restoration and coastal protection projects. To meet these needs, methods must be available for predicting dune recovery as well as dune erosion. In the present study, an empirical dune growth model (EDGR) was developed to predict the evolution of the primary foredune of a barrier island. Within EDGR, an island is represented as a sum of Gaussian shape functions rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“…HOUSER et al (2015) [77] conducted field measurements at the northern Gulf of Mexico (Santa Rosa Island, Florida and Galveston Island, Texas) and found that for predicting the evolution of a barrier island's foredune height a parameterized sigmoid growth curve can be applied. These results are supported by DALYANDER et al (2020) [12], who developed an empirical dune growth model to predict the evolution of the foredune of a barrier island for the example of the Dauphin Island (Alabama). This could influence the observed variability in sediment accumulation independently of the sand trapping configurations.…”
Section: Dune Volume Changessupporting
confidence: 57%
See 3 more Smart Citations
“…HOUSER et al (2015) [77] conducted field measurements at the northern Gulf of Mexico (Santa Rosa Island, Florida and Galveston Island, Texas) and found that for predicting the evolution of a barrier island's foredune height a parameterized sigmoid growth curve can be applied. These results are supported by DALYANDER et al (2020) [12], who developed an empirical dune growth model to predict the evolution of the foredune of a barrier island for the example of the Dauphin Island (Alabama). This could influence the observed variability in sediment accumulation independently of the sand trapping configurations.…”
Section: Dune Volume Changessupporting
confidence: 57%
“…The coastal dunes are already more established at the eastern end than the western end, see Figure 13. This might explain more rapid growth at the western end than at the eastern end, given that dune growth tends to follow a sigmoid growth curve [12,77]. HOUSER et al (2015) [77] conducted field measurements at the northern Gulf of Mexico (Santa Rosa Island, Florida and Galveston Island, Texas) and found that for predicting the evolution of a barrier island's foredune height a parameterized sigmoid growth curve can be applied.…”
Section: Dune Volume Changesmentioning
confidence: 99%
See 2 more Smart Citations
“…The simulations included a static sea-level change and geomorphologic evolution for various simulated storms with and without a suite of restoration actions. Geomorphologic predictions were made using numerical models that capture long-term alongshore sediment transport (Delft 3D), shortterm storm-induced impacts (XBeach; Roelvink et al 2009), and dune building and recovery (empirical dune growth model; Dalyander et al 2020). The simulations highlighted in this study were the contemporary geomorphology and the future predicted geomorphology with a 0.96-m static sea-level change and subsequent geomorphic evolution over a decade with high storminess (i.e., less than four storms that result in overwash; 29% probability of occurrence based on storm climatology; Mickey et al 2020).…”
Section: Future Island Configurationsmentioning
confidence: 99%